Thinking Outside the Box in Boston: The Impact of Green Building on Urban Systems and Municipal Infrastructure. - Chapin, Ela.; Heaviland, Minona.; Minzer, Ellen.; Young, Stefanie. (Tufts University. Tisch Library., 2018)
2005 M.A. in Urban and Environmental Policy and Planning Field Project. Client: The Green Roundtable.